Studi Kompetensi di Sektor Publik dan Kasusnya di Samarinda, Indonesia: The Studies of Competencies in The Public Sector and Its Case in Samarinda, Indonesia - Sartika, Dewi; Andi Wahyudi; Tri Noor Aziza; Maria Agustini Permata Sari; Armelya Trinita Fornia; Novia Leny Christine; Yurike Anindyasari (Jurnal Riset Inossa : Media Hasil Riset Pemerintahan, Ekonomi dan Sumber Daya Alam, 2025)
Competency development in the public sector is intended to increase the performance of public sector organization and public service performance. Many studies of this issue have been conducted, but competence development practice remains critical problems in Indonesian public sector. This paper aims to analyze the trend of competency development studies in the public sector and to examine the competency development of civil servants in Samarinda Municipality. This study combines two research methods. First, it uses a semi-literature review with a bibliometric analysis. The data are collected from Scopus database and VOSviewer software is used to analyze, visualize, and explore maps based on network data. Second, the case study strategy is applied to capture the practice of competence development in the public sector. The locus is the Cooperative, Small and Medium Enterprises (CSMEs) Agency in Samarinda Municipality. This study found out the positive trend of competency development in the last several years, especially since 2018. Competency development topics are often presented together with various keywords. But education is the keyword that appears most often in search results. The next most influential keywords are people, public sector, articles, leadership, and competence. In short, the topic of competency development in the public sector is interesting and widely available for elaboration for future research. Since 2018, this topic has achieved a higher number of publications. In addition, combining the competency development keywords with other keywords can produce new research topic variants and new knowledge related to competency development topics in the public sector in both developed and developing countries. In practice, competency development at the locus is a portrait of competency development practices in Samarinda City as the capital city of East Kalimantan province in Indonesia. In addition to having various opportunities from the external side, but also has weaknesses from the internal side. If it is not followed up immediately, it will be difficult for the unit of analysis to support the mayor's vision of creating new entrepreneurs in the city. This example of developing civil servants needs to be compared with practices in other local governments. This issue is much more discussed along with education keyword, therefore there is a huge opportunity to explore this topic in the public sector. Furthermore, the practice of competency development at the CSMEs is limited although it has a huge opportunity to make use its potency.